2010
DOI: 10.1002/art.27200
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐27 inhibits human osteoclastogenesis by abrogating RANKL‐mediated induction of nuclear factor of activated T cells c1 and suppressing proximal RANK signaling

Abstract: Objective. Interleukin-27 (IL-27) has stimulatory and regulatory immune functions and is expressed in rheumatoid arthritis (RA) synovium. This study was undertaken to investigate the effects of IL-27 on human osteoclastogenesis, to determine whether IL-27 can stimulate or attenuate the osteoclast-mediated bone resorption that is a hallmark of RA.Methods. Osteoclasts were generated from bloodderived human CD14؉ cells. The effects of IL-27 on osteoclast formation were evaluated by counting the number of tartrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 53 publications
4
74
0
Order By: Relevance
“…is reported to inhibit RANKL-mediated osteoclastogenesis (18). In Ovx estrogen-deficient conditions, there is an increased rate of bone resorption.…”
Section: Il-27 Negatively Regulates Osteoclastogenesis Through Egr-2-mentioning
confidence: 99%
See 1 more Smart Citation
“…is reported to inhibit RANKL-mediated osteoclastogenesis (18). In Ovx estrogen-deficient conditions, there is an increased rate of bone resorption.…”
Section: Il-27 Negatively Regulates Osteoclastogenesis Through Egr-2-mentioning
confidence: 99%
“…A report by Kalliolias et al (18) has also shown the direct effect of IL-27 on osteoclastogenesis by suppressing responses of osteoclast precursors to RANKL. IL-27 inhibits human osteoclastogenesis by abrogating RANKL-mediated induction of NFATc1 and suppressing proximal RANK signaling (18). In osteoblasts, IL-27 stimulated STAT-3 activation but had no significant effect on alkaline phosphatase activity and proliferation of osteoblasts (17).…”
mentioning
confidence: 96%
“…IL-27 is a cytokine that probably acts in the regulation of bone homeostasis. This cytokine is responsible for decreasing bone degradation by suppressing the expression of RANK precursors (e.g., NFATc1) [24]. Therefore, it is possible to suggest that IL-27 makes an important contribution, with a positive balance regarding cytokine-mediated inflammatory diseases (e.g., osteoporosis).…”
Section: Discussionmentioning
confidence: 99%
“…In certain conditions, TLRs and certain cytokines inhibited RANK, RANKL and osteoclasts. For example, IL-10, a immune modulator, inhibited osteoclasts by preventing nuclear translocation of NFATc1 and RANKL-induced expression of NFATc1, Jun and Fos [57], IL4 and IL27 shared the similar mechanism in suppressing NFATc1 induced by RANKL [58,59], and TLRs and γ-interferon inhibited RANK and osteoclast precursors [60]. In addition, in osteoclasts, it has been shown that Toll-like receptor 2 (TLR2) that mediates inflammation and bone metabolism by activating RANKL, NFATc1, NF-κB, and others [61]; protein inhibitor of activated STAT3 (PIAS3) inhibits the promoter of NFATc1 [62]; Notch recruits NF-κB p65 to the promoter of NFATc1 for transcription activation [63]; and vitamin D inhibits the NFAT transcriptional activation [64].…”
Section: Regulation Of Nfatc1 and Osteoclasts By Inflammationmentioning
confidence: 99%